2020
DOI: 10.3390/plants9020175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cross-Species Transferability of SSR Markers in Foeniculum vulgare

Abstract: Fennel (Foeniculum vulgare) is a species belonging to the Apiaceae family, well known for its nutritional and pharmacological properties. Despite the economic and agricultural relevance, its genomic and transcriptomic data remain poor. Microsatellites—also known as simple sequence repeats (SSRs)—are codominant markers widely used to perform cross-amplification tests starting from markers developed in related species. SSRs represent a powerful tool, especially for those species lacking genomic information. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Microsatellite—alias simple sequence repeats (SSR)-markers, are co-dominantly inherited, ubiquitous, highly polymorphic, and have found large application in plant breeding and phylogenetic studies because of their simple application through conventional PCR protocols [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Unlike single nucleotide polymorphisms (SNPs), which have become the gold standard among molecular markers, SSRs show the advantage of being multi-allelic and highly informative, characterized by a certain level of transferability between related specie [ 17 , 18 , 19 , 20 ], and are easily and automatically scorable.…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellite—alias simple sequence repeats (SSR)-markers, are co-dominantly inherited, ubiquitous, highly polymorphic, and have found large application in plant breeding and phylogenetic studies because of their simple application through conventional PCR protocols [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Unlike single nucleotide polymorphisms (SNPs), which have become the gold standard among molecular markers, SSRs show the advantage of being multi-allelic and highly informative, characterized by a certain level of transferability between related specie [ 17 , 18 , 19 , 20 ], and are easily and automatically scorable.…”
Section: Introductionmentioning
confidence: 99%
“…The development of species-specific SSR markers is very costly and time-consuming, so the information on SSR markers for economically less important species is still limited. A strategy that can overcome this problem is to utilize the cross-amplification ability of SSR markers to access the genetic diversity of the related species (Celiński et al 2013;Aiello et al 2020). Several studies on the SSR marker transferability were conducted among many taxonomic levels.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been demonstrated that increasing the genetic distance among taxa may reduce the marker transfer efficiency [32,33]. For example, some recent studies aimed to test the SSR transferability among genera of the same family (e.g., Cactaceae, Arecaceae and Apiaceae) and achieved success rates of approximately 23-35% [34][35][36]. At the genus level, the percentage of SSR transferability among species rises to 80-85% [37,38] or even higher (90-98%) when EST-SSR are considered [39,40].…”
Section: Discussionmentioning
confidence: 99%